Pathogenic Mechanisms Underlying Cirrhotic Cardiomyopathy - Liu, Hongqun; Nguyen, Henry H.; Yoon, Ki Tae; Lee, Samuel S. (Frontiers in Network Physiology, 2022)
Abstract: Cardiac dysfunction associated with cirrhosis in the absence of preexisting heart disease is a condition known as cirrhotic cardiomyopathy (CCM). Cardiac abnormalities consist of enlargement of cardiac chambers, attenuated systolic and diastolic contractile responses to stress stimuli, and repolarization changes. CCM may contribute to cardiovascular morbidity and mortality after liver transplantation and other major surgeries, and also to the pathogenesis of hepatorenal syndrome. The underlying mechanisms of CCM are poorly understood and as such medical therapy is an area of unmet medical need. The present review focuses on the pathogenic mechanisms responsible for development of CCM. The two major concurrent mechanistic pathways are the inflammatory phenotype due to portal hypertension, and protein/lipid synthetic/metabolic defects due to cirrhosis and liver insufficiency. The inflammatory phenotype arises from intestinal congestion due to portal hypertension, resulting in bacteria/endotoxin translocation into the systemic circulation. The cytokine storm associated with inflammation, particularly TNFα acting via NFκB depresses cardiac function. They also stimulate two evanescent gases, nitric oxide and carbon monoxide which produce cardiodepression by cGMP. Inflammation also stimulates the endocannabinoid CB-1 pathway. These systems inhibit the stimulatory beta-adrenergic contractile pathway. The liver insufficiency of cirrhosis is associated with defective synthesis or metabolism of several substances including proteins and lipids/lipoproteins. The protein defects including titin and collagen contribute to diastolic dysfunction. Other protein abnormalities such as a switch of myosin heavy chain isoforms result in systolic dysfunction. Lipid biochemical changes at the cardiac sarcolemmal plasma membrane result in increased cholesterol:phospholipid ratio and decreased membrane fluidity. Final common pathway changes involve abnormal cardiomyocyte intracellular ion kinetics, particularly calcium. In conclusion, cirrhotic cardiomyopathy is caused by two pathways of cellular and molecular dysfunction/damage due to hepatic insufficiency and portal hypertension.